Новые виды рода Propontocypris (Crustacea, Ostracoda) с литорали Курильских островов - Шорников, Е.И. (Вестник зоологии, 1973)
The group postconcava is distinguished which unites the related species Propontocypris (Schedopontocypris?) postconcava sp. n., P. (S.?) maculata sp. n., P. (S.?) ovata sp. n. The group is the most similar to the Schedopontocypris Maddox, 1969, subgenus but by some characters it does not coincide with the diagnosis of the latter.